Iron Sulfide Enhanced the Dechlorination of Trichloroethene by Dehalococcoides mccartyi Strain 195 - Li, Yaru; Zhao, He-Ping; Zhu, Lizhong (Frontiers in Microbiology, 2021)
Iron sulfide (FeS) nanoparticles have great potential in environmental remediation. Using the representative species Dehalococcoides mccartyi strain 195 (Dhc 195), the effect of FeS on trichloroethene (TCE) dechlorination was studied with hydrogen and acetate as the electron donor and carbon source, respectively. With the addition of 0.2 mM Fe2+ and S2-, the dechlorination rate of TCE was enhanced from 25.46±1.15 to 37.84±1.89 μmol•L-1•d-1 by the in situ formed FeS nanoparticles, as revealed through X-ray diffraction (XRD). Compare the tceA gene copy numbers between with FeS and without FeS, real-time PCR indicated that the abundance of the tceA gene increased from (2.83±0.13)×107 to (4.27±0.21)×108 copies/mL on day 12. The transcriptional activity of key genes involved in the electron transport chain was upregulated after the addition of FeS, including those responsible for the iron-sulfur cluster assembly protein gene (DET1632) and transmembrane transport of iron (DET1503, DET0685), cobalamin (DET0685, DET1139), and molybdenum (DET1161) genes. Meanwhile, the reverse transcription of tceA was increased approximately 5 times on the 12th day. These upregulations together suggested that the electron transport of Dhc 195 was enhanced by FeS for apparent TCE dechlorination. Overall, the present study provided an eco-friendly and effective method to achieve high remediation efficiency for organohalide-polluted groundwater and soil.